A feminist ethnography of secure wards for women with learning disabilities : locked away - Fish, Rebecca, 1972- (New York : Routledge, 2018)
"What is life like for women with learning disabilities detained in a secure unit? This book presents a unique ethnographic study conducted in a contemporary institution in England. Rebecca Fish takes an interdisciplinary approach, drawing on both the social model of disability and intersectional feminist methodology, to explore the reasons why the women were placed in the unit, as well their experiences of day-to-day life as played out through relationships with staff and other residents. She raises important questions about the purpose of such units and the services they offer. Through making the women's voices heard, this book presents their experiences and unique perspectives on topics such as seclusion, restraint, and resistance. Exploring how the ever present power disparity works to regulate women's behaviour, the book shows how institutional responses replicate?women's?bad experiences from?the past, and how women's responses are seen?as pathological.?It demonstrates that women are not passive recipients of care,?but?shape?their own identity and futures, sometimes by resisting the norms expected of them (within allowed limits) and sometimes by transgressing the rules.? These insights thus challenge traditional institutional accounts of gender, learning disability and deviance and highlight areas for reform in policy, practice, methodology, and social theory. This groundbreaking book will be of interest to scholars, students, policy-makers and advocates working in the fields of learning disability and disability studies more widely, gender studies and sociology."--Provided by publisher.
Acknowledgements -- One year, one unit -- Learning disabled women in secure services -- Life on the unit -- Relationships on the locked ward -- Difficult women? -- Moving on : progression through services -- Intersections : making conclusions -- Index.
OCLC-licensed vendor bibliographic record.
Keywords: Learning disabled women -- Institutional care -- Great Britain; POLITICAL SCIENCE -- Public Policy -- Social Security; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; MEDICAL / Nursing / Mental Health; SOCIAL SCIENCE / Social Work; MEDICAL / Nursing / Reference